Paralytic ileus in the United States: A cross-sectional study from the national inpatient sample - Shantanu Solanki; Raja Chandra Chakinala; Khwaja Fahad Haq; Jagmeet Singh; Muhammad Ali Khan; Dhanshree Solanki; Manasee J Vyas; Asim Kichloo; Uvesh Mansuri; Harshil Shah; Achint Patel; Khwaja Saad Haq; et al. (SAGE Open Medicine, 2020)
Introduction: Paralytic ileus is a common clinical condition leading to significant morbidity and mortality. Most studies to date have focused on postoperative ileus, a common but not exclusive cause of the condition. There are limited epidemiological data regarding the incidence and impact of paralytic ileus and its relationship to other clinical conditions. In this cross-sectional study, we analyzed national inpatient hospitalization trends, demographic variation, cost of care, length of stay, and mortality for paralytic ileus hospitalizations as a whole. Methods: The National Inpatient Sample database was used to identify all hospitalizations with the diagnosis of paralytic ileus (International Classification of Diseases, 9th Revision code 560.1) as primary or secondary diagnosis during the period from 2001 to 2011. Statistical analysis was performed using Cochran–Armitage trend test, Wilcoxon rank sum test, and Poisson regression. Results: In 2001, there were 362,561 hospitalizations with the diagnosis of paralytic ileus as compared to 470,110 in 2011 (p < 0.0001). The age group 65–79 years was most commonly affected by paralytic ileus throughout the study period. In-hospital all-cause mortality decreased from 6.03% in 2001 to 5.10% in 2011 (p < 0.0001). However, the average cost of care per hospitalization increased from US$19,739 in 2001 to US$26,198 in 2011 (adjusted for inflation, p < 0.0001). Conclusion: There was a significant rise in the number of hospitalizations of paralytic ileus with increased cost of care and reduced all-cause mortality.